2019
DOI: 10.1016/j.foodchem.2019.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of navy bean (Phaseolus vulgaris) protein concentrates obtained by pneumatic tribo-electrostatic separation

Abstract: A sustainable, chemical-free dry tribo-electrostatic separation approach was employed to fractionate navy bean flour. The resulting protein-enriched fractions had 36-38% protein on a moisture free basis, accounting for 43% of the total available protein. SDS-PAGE analysis of the dry-enriched protein fractions showed a similar protein profile to that of the original navy bean flour. The functional properties of these fractions were examined and compared with the commercial soybean protein concentrate as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…Later, single- and multi-stage tribo-electrostatic bioseparation processes for dry fractionation of protein concentrate found that the two-stage approach resulted in a protein-rich fraction yield of 38% accounting for 60% of the total protein which was a significantly higher than that of the optimized single-stage triboelectrostatic separation [127]. Similarly, Jafari et al [124] and Tabtabaei et al [128] examined the physiochemical and functional properties of navy bean protein concentrated using triboelectrostatic separation. They found that electrostatically separated increased from 25.4% to 43.0% total protein yield of original navy bean flour, the protein fractions protein fractions exhibited superior solubility, superior emulsion stability, foam expansion and foam volume stability compared to the wet-fractionated navy bean protein isolate.…”
Section: Protein Isolation Methods and Extractionmentioning
confidence: 99%
“…Later, single- and multi-stage tribo-electrostatic bioseparation processes for dry fractionation of protein concentrate found that the two-stage approach resulted in a protein-rich fraction yield of 38% accounting for 60% of the total protein which was a significantly higher than that of the optimized single-stage triboelectrostatic separation [127]. Similarly, Jafari et al [124] and Tabtabaei et al [128] examined the physiochemical and functional properties of navy bean protein concentrated using triboelectrostatic separation. They found that electrostatically separated increased from 25.4% to 43.0% total protein yield of original navy bean flour, the protein fractions protein fractions exhibited superior solubility, superior emulsion stability, foam expansion and foam volume stability compared to the wet-fractionated navy bean protein isolate.…”
Section: Protein Isolation Methods and Extractionmentioning
confidence: 99%
“…is one of the major constituents of dry beans, and could represent a major product after isolating other valuable components such as protein concentrates. 15 It would be promising to develop new applications using the starch component of navy bean. For example, studies on films produced from dry bean starches have just emerged.…”
Section: Starchmentioning
confidence: 99%
“…Recently, gluten‐free pasta has also developed using dry bean flours, in which the texture properties were mainly affected by the starch content 14 . Starch is one of the major constituents of dry beans, and could represent a major product after isolating other valuable components such as protein concentrates 15 . It would be promising to develop new applications using the starch component of navy bean.…”
Section: Introductionmentioning
confidence: 99%
“…The design of roll‐type corona–electrostatic separator depends on various factors such as roll speed, high voltage amount of corona, and electrostatic electrode that improve the efficiency of process. Tabtabaei, Konakbayeva, Rajabzadeh, and Legge () showed that the functional properties of navy bean protein concentrates obtained by pneumatic triboelectrostatic separation applied a sustainable, chemical‐free dry triboelectrostatic separation method for soybean protein concentrate as well as navy bean protein. They reported that the functional properties of these fractions were examined and compared with the commercial soybean protein concentrate as well as navy bean protein isolate obtained by a conventional wet fractionation process.…”
Section: Introductionmentioning
confidence: 99%